The role of enterosorbtion in treatment of bacterial diarrhea in children - O.I. Nyrkova; L.A. Alekseyeva; M.K. Bekhtereva; T.V. Bessonova ("Paediatrician" Publishers LLC, 2011)
Authors studied clinical and laboratory efficacy of natural enterosorbate Filtrum-STI in treatment of acute bacterial diarrhea in patients 1-14 years old. The drug has significant detoxication effect resulting in the dynamics of infection syndrome and terms of endotoxicosis laboratory markers normalization. This sorbate has protective effect on obligatory micro flora of intestinum. Key words: children, bacterial intestinal infections, endotoxicosis, enterosorption.